The day hospital in the community - M.J. Hattingh (AOSIS, 1979)
The term Day Hospital is attached to centres where primary health care is rendered, not necessarily only during the day, but rather to a community who cannot readily reach other existing facilities. The first day hospital was opened in 1860 in Cape Town for this reason; it could then be seen as an extended arm of the hospital to the community. Numerous conditions are treated that do not need any hospitalisation or necessitate the direct attention of a medical practitioner.